Clinical and morphological presentations of acute coronary syndrome without coronary plaque rupture — An intravascular ultrasound study. (1st October 2016) - Tsujita, Kenichi; Yamanaga, Kenshi; Komura, Naohiro; Sakamoto, Kenji; Miyazaki, Takashi; Oimatsu, Yu; Ishii, Masanobu; Tabata, Noriaki; Akasaka, Tomonori; Sueta, Daisuke; Yamamoto, Eiichiro; Yamamuro, Megumi; et al.
Abstract: Background: Although acute coronary syndrome (ACS) mainly arises from plaque ruptures (PR), precise mechanisms underlying ACS without PR are unknown. We sought to examine clinical, angiographic and intravascular ultrasound (IVUS) characteristics of ACS without PR. Methods and results: Culprit lesions of 161 ACS patients were categorized by the presence or absence of PR (PR group: n = 57, Non-PR group: n = 104). Lower abdominal circumference (86 ± 10 cm vs 90 ± 9 cm, p = 0.02), lower prevalence of myocardial infarction (53% vs 82%, p = 0.0002), and higher prevalence of definite vasospasm (15% vs 2%, p = 0.006) were found in Non-PR group. Morphologically, Non-PR group was associated with simpler Ambrose classification (36% vs 14%, p = 0.004), less hypoechoic plaque (45% vs 65%, p = 0.04) and lower incidence of IVUS-detected thrombus (21% vs 54%, p < 0.0001), compared with PR group. On quantitative IVUS, although minimum lumen area (MLA) was similar between the groups, vessel (14.2 ± 5.4 mm 2 vs 17.5 ± 5.1 mm 2, p = 0.0002) and plaque (11.6 ± 5.0 mm 2 vs 14.9 ± 4.9 mm 2, p < 0.0001) areas were significantly smaller at MLA site in Non-PR group than in PR group. On multivariate analysis, average plaque area was only an independent IVUS-predictor of non-rupture ACS (odds ratio: 0.85, p = 0.01). Conclusion: Compared to ACS with PR, non-rupture ACS arise from more hyperechoic (allegedly "stable") plaque with smaller vessel and plaque area, leading to lower incidence of thrombotic occlusion. Coronary vasospasm might be a possible pathogenic mechanism underlying non-rupture ACS.